Perfect wives, other women : adultery and inquisition in early modern Spain - Dopico Black, Georgina (e-Duke books scholarly collection., 2001)
Close readings of canonical Spanish "Golden Age" and Latin American "colonial" texts, drawing heavily on the findings and strategies of psychoanalytic criticism, gender studies and Marxism, and offering an understanding of a repres.